Job Satisfaction and Workplace Representation in Europe - Addison, John (2024)
The backdrop to this inquiry into the relationship between worker job satisfaction and workplace representation in European nations is twofold. The first is that the bulk of research has focused on union membership and job satisfaction in Anglophone nations with their very different industrial relations systems and bargaining arrangements. The second and more immediate context is the dramatic shift from negative to positive in the association between union membership and job satisfaction (inter al.) observed in the most recent literature. Using data on 28 European nations from the last two waves of the European Working Conditions Survey, however, we report that workers in establishments with formal workplace representation record lower job satisfaction than their counterparts in plants without such representation. These findings of conditional correlation are then upgraded by constructing a pseudo-panel with cohort fixed effects to take account of unobserved worker heterogeneity. First-difference estimates suggest that the negative relationship between worker representation and job satisfaction found in cross section continues to hold. Next, an endogenous treatment effects model is deployed to address the possible endogeneity of worker representation. The results are supportive of a causal negative relationship between job satisfaction and worker representation. One interpretation of our findings is that in the matter of the association between unions and job satisfaction the jury is still out.